1619 Evaluation of Referrals to The Maxillofacial on Call Service Over A Seven-Year Period in A Busy Tertiary Trauma Centre and Teaching Hospital. (12th October 2021) - Musa, A; Lin, Y; Collard, B
Abstract: Aim: University Hospitals Plymouth is the only designated adult major trauma centre for the south west of England, also serving secondary care to a catchment of 450, 000 patients. The on call maxillofacial service receives numerous referrals daily, which began to be recorded in a trauma database populated on a daily basis. Our study aims to evaluate these referrals with a view to classifying them and identifying service provision needs; improve support and training of the junior team; and understand patient demographics. Method: There were 3717 referrals recorded between 7 th January 2014 and 7 th January 2021. All referrals were taken into account; from the emergency department; from primary care providers; from other hospital departments; and directly from patients themselves. Both adult and paediatric cases were included. Results: Of these 3717 referrals, 2122 (57%) were pertaining to male patients. Adult patients accounted for 85% of the referrals and 1200 (32%) of all patients were referred for soft tissue injury. Around 20% of patients attended with facial swellings. 1090 (29%) patients were able to have treatment under a local anaesthetic, whilst 959 (26%) required admission. Most common fractures were nasal (8%), followed by orbital wall (6%) and mandibular fractures (4%). Conclusions: Evaluation of the database shows a slight prevalence of male attenders, particularly in cases involving trauma. Management of soft tissue injuries under local anaesthetic is an important topic during the induction of new junior trainees to the department, in accordance with the expected service provision. Furthermore, the large sample has allowed for epidemiologic analysis and interventions.